2021
DOI: 10.3390/lubricants9040045
|View full text |Cite
|
Sign up to set email alerts
|

Novel Uses of Al2O3/Mos2 Hybrid Nanofluid in MQCL Hard Milling of Hardox 500 Steel

Abstract: In recent years, the application of environmentally friendly cutting fluids in the metal cutting industry has been a growing concern in all over the world. In this study, the minimum quantity cooling lubrication (MQCL) technique, which uses very small amount of cutting oil, is motivated to apply to the hard milling process of Hardox 500 steel. Further, rice bran oil, a natural biodegradable oil, is used as the base fluid of Al2O3/MoS2 hybrid nanofluid. ANOVA analysis is used to study the influences of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, the nanoparticles easily adhere to the top of the cutting edge, causing scratches on the machined surface. This phenomenon is formed and lost continuously, thus deteriorating surface quality [34]. For high cutting speeds, the workpiece shear strength decreases because the cutting heat is high enough to reduce the required cutting forces and positively affect the machined surface finish.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the nanoparticles easily adhere to the top of the cutting edge, causing scratches on the machined surface. This phenomenon is formed and lost continuously, thus deteriorating surface quality [34]. For high cutting speeds, the workpiece shear strength decreases because the cutting heat is high enough to reduce the required cutting forces and positively affect the machined surface finish.…”
Section: Resultsmentioning
confidence: 99%
“…Duc et al [246] studied the effects of nanoparticles used as additive in nanofluid on cutting performance and surface roughness in the minimum quantity cooling lubrication (MQCL) technique. They found the outstanding lubrication and cooling effects of Al 2 O 3 /MoS 2 hybrid nanofluid with the evaluation of different nanoparticle concentrations, cutting speeds, and feed rates.…”
Section: Lubrication Of Machinery Manufacturingmentioning
confidence: 99%
“…The study showed that the increase in the concentration of SiO 2 nanoparticles promoted the growth of the tool-chip interface protective film, and the film that formed on the machined surface improved the surface quality of the workpiece and reduced the cutting temperature and cutting force [11]. Long T M et al used MoS 2 nanosheet nanofluid and Al 2 O 3 /MoS 2 hybrid nanofluid in minimum quantity cooling lubrication (MQCL) hard milling, and the obtained results indicated that better cooling/better effects and good surface quality were achieved [12,13].…”
Section: Introductionmentioning
confidence: 99%